Implementasi Politik Etis Terhadap Pendidikan Pribumi di MULO Surabaya 1914-1942 - Syahvier Sukmana Basyasah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the implementation of the Ethical Policy toward indigenous education at Meer Uitgebreid Lager Onderwijs (MULO) in Surabaya during 1914–1942. It focuses on the selection process of indigenous students, the implementation of the educational system, and its impact on indigenous society. This research employs a qualitative historical method through heuristics, source criticism, interpretation, and historiography. Data were collected from colonial archives, Dutch-language newspapers, official government documents, and relevant literature. The findings show that access to MULO remained highly selective through entrance examinations, academic ranking, and Dutch language proficiency requirements. The implementation of the Ethical Policy was reflected in the establishment of a modern educational system designed to meet the administrative needs of the colonial government. At the same time, MULO provided opportunities for social mobility by enabling indigenous graduates to work as teachers, administrative officers, and office employees. Moreover, the institution contributed to the emergence of an educated indigenous elite with growing social and political awareness, demonstrating that MULO functioned not only as an instrument of colonial rule but also as a space that indirectly fostered Indonesian nationalism.